Comparison of the umami taste and aroma of dried Suillus granulatus packed using four different packaging methods. (1st January 2022) - Feng, Yao; Xin, Guang; Wei, Yunyun; Xu, Heran; Sun, Libin; Hou, Zhenshan; Sun, Bingxin
Highlights: Dried S. granulatus had better umami taste and aroma in transparent packaging. The umami taste and aroma were better after four to six months of storage. Light could be used as a treatment technology to improve the umami taste and aroma. Ketones and pyrazines were more abundant in transparent packaging. Abstract: Umami and aroma are important flavor qualities of edible mushrooms, and packaging can maintain or improve the flavor during storage. This study explored the effects of light-proof packaging (LPP), light-transparent packaging (LTP), vacuum light-proof packaging (VLPP), and vacuum light-transparent packaging (VLTP) on umami taste and aroma of dried Suillus granulatus . Monosodium glutamate-like amino acid content, equivalent umami concentration, and electronic tongue umami sensory scores in VLTP were higher at 2, 4, and 6 months and higher in LTP at 8 and 10 months. Principal component analysis of aroma components showed that the comprehensive scores were higher for the transparent packaging. Ketones and pyrazines were more abundant in transparent packaging. Flavor quality was better at 4–6 months, based on the equivalent umami concentration and the concentration of eight-carbon compounds that contribute to aroma. Transparent packaging is a promising way to optimize the flavor of dried Suillus granulatus .